Gait analysis using load-controlled single- and split-belt treadmills - Ouchi, Y.; Tsujiuchi, N.; Ito, A.; Hirose, K. (Proceedings, 2020)
We developed a self-paced load-controlled treadmill with two built-in force plates to enhance lower limb muscles. Since the load can be changed freely with a load-controlled treadmill, it can be widely utilized in fields such as rehabilitation and training. In this paper, we experimentally investigated the difference between single-belt and split-belt load-controlled treadmills with two subjects, who walked 30 s with a constant load r = 0, 5, 10, 15% based on the maximum driving force on both treadmills. Our result showed that the angular range of the motion of the ankle joints when walking on a single-belt treadmill was up to 2.68 times larger than walking on a split-belt treadmill. The ground reaction force reading showed that the ankle joint moment on a single-belt was larger during the terminal stance, suggesting that single-belt treadmills more effectively enhance lower limb muscles.